NEW LOCALITIES OF RARE FLORA SPECIES IN THE KAZAKH PART OF THE KYRGYZ ALATAU RANGE (Eurasian Journal of Ecology, 2026)
The Kyrgyz Alatay, located at the junction of the Northern and Western Tien Shan ranges, forms an ecotonal zone between the Chuy Valley to the north and the Kochkor, Susamyr, and Talas valleys to the south. Its border position between different orographic and climatic regions determines the mosaic nature of landscapes and, consequently, the high diversity of various geo-elements within the flora.According to recent studies, the flora of the Kyrgyz Alatay (within Kazakhstan) includes 1,473 species of vascular plants, belonging to 504 genera and 94 families, which represents almost 50% of the species of the Northern Tien Shan flora as a whole. To date, between 41 and 46 rare species included in the national Red Book have been recorded in the Kazakh (western) part of the range by various authors, five of which are endemic to the Kyrgyz Alatay.Field research conducted in 2022–2025 led to the identification of 15 new localities of rare species in the Kazakh part of the Kyrgyz Alatay. Most species are threatened; however, some taxa, such as Allium suworowii, Celtis caucasica, Pyrus regelii, and Zabelia corymbosa, form stable local populations.The obtained results supplement the information on the distribution and status of populations of rare species in the flora of the western part of the Kyrgyz Alatay and emphasize the need to continue monitoring in this biogeographically significant ecotonal region.Keywords: Kyrgyz Alatau Range, rare species, flora.